2015
DOI: 10.1002/jcb.25166
|View full text |Cite
|
Sign up to set email alerts
|

CDC42 Gtpase Activation Affects Hela Cell DNA Repair and Proliferation Following UV Radiation‐Induced Genotoxic Stress

Abstract: Cell division control protein 42 (CDC42) homolog is a small Rho GTPase enzyme that participates in such processes as cell cycle progression, migration, polarity, adhesion, and transcription. Recent studies suggest that CDC42 is a potent tumor suppressor in different tissues and is related to aging processes. Although DNA damage is crucial in aging, a potential role for CDC42 in genotoxic stress remains to be explored. Migration, survival/proliferation and DNA damage/repair experiments were performed to demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 46 publications
2
19
0
5
Order By: Relevance
“…Our results demonstrated that ROS production increased in ADMSCs from aged rats and that this was attenuated by CASIN. These data, together with the observation that Cdc42 regulates NADPH oxidase activation (Ascer et al 2015;Qian et al 2005;Wang et al 2012b) suggests the possibility that inhibition of Cdc42 leads to an improvement of ADMSC proliferation and differentiation via suppression of NADPH oxidase activity.…”
Section: Discussionmentioning
confidence: 76%
“…Our results demonstrated that ROS production increased in ADMSCs from aged rats and that this was attenuated by CASIN. These data, together with the observation that Cdc42 regulates NADPH oxidase activation (Ascer et al 2015;Qian et al 2005;Wang et al 2012b) suggests the possibility that inhibition of Cdc42 leads to an improvement of ADMSC proliferation and differentiation via suppression of NADPH oxidase activity.…”
Section: Discussionmentioning
confidence: 76%
“…DNA damage can be evaluated by comet assay 18 19 , which was employed in this study to determine whether HBx could result in DNA damage. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to certify that the selected inducers would actually activate RhoGTPases, we conducted an activity assay, to measure GTP-bound Cdc42, Rac and RhoA proteins. The following protocol was adapted from Espinha et al ., 2016 and Ascer et al ., 2015 33 , 34 . E. coli (strain BL21-DE3) bacteria were transformed via thermal shock with plasmids containing the sequence encoding the fusion protein RBD-GST (Rhotekin-Binding Domain-fused to Glutathione S-Transferase) or PBD-GST (PAK1-Binding Domain fused to Glutathione-S Transferase), which was kindly donated by Gary M. Bokoch from Scripps Research Institute, La Jolla, CA, USA.…”
Section: Methodsmentioning
confidence: 99%
“… 33 and Ascer et al . 34 . SHEDs protein lysates from a control sample were obtained from 10-mm dishes at approximately 60% confluence that were serum starved for 18 h and then treated 100 ng/ml of epidermal growth factor – EGF (Peprotech, NJ, USA) to activate Cdc42 21 ( http://www.cytoskeleton.com/cn02 ), 25 ng/ml of EGF to activate Rac1/2/3 22 ( http://www.cytoskeleton.com/cn02 ) and 30 ug/ml of calpeptin (Tocris, UK) to activate RhoA 23 ( http://www.cytoskeleton.com/cn01 ).…”
Section: Methodsmentioning
confidence: 99%